Image Schema Analysis on Psalm 23: A Study of Metaphor Based on Cognitive Theory - Paulus Subiyanto; Ida Bagus Putra Yadnya; 3Aron Meko Mbete; Frans I Made Brata (The Doctoral Studies Program of Linguistics of Udayana University, 2019)
This article aims to identify what types of image schemas operating in Psalm 23 ―TheLord is My Shepherd. This text is very old and full with metaphors. According to the theory ofConceptual Metaphor, metaphorical phenomena are not merely as a linguistic matter, but ratheras a process of cognition by which humans understand the reality (Lakoff and Johnson,1980).Unconsciously, conceptual metaphor generates metaphorical expressions in our daily life.Behind the conceptual metaphor, there are image schemas serving as a pre-conceptual structurederived from physical experiences, cultural background, and ideology of a nation. Image-schemais a recurring structure within our cognitive process (Johnson,1987).The Psalm 23 ―The Lord is my Shepherd‖ consists of 6 verses, each may be contained of morethan one sentence or phrase. It was written by King David about the fifth and the tenth centuryB.C. to show the goodness of God, and His close relationship with His people. God is portrayedas a good shepherd caring deeply to His cattle. Mapping method is adopted to construct themeaning of metaphor in which The Lord as Target Domain and Shepherd as Source Domain.Then, each verse is analyzed to find image schemas involved in the text. As the result, there areseven types of image schemas in Psalm 23: container, path, link, force, attraction, blockage, andremoval of restraints. Based on these findings, it can be concluded that image schema as anelementary part of conceptual metaphor has potential to be an analysis tool to discover themeaning of metaphorical texts.